Odpowiedzi

2010-04-15T13:40:40+02:00
3x + 2x =5x
6x - x =5x
- 8x + 5x =-3x
2a + 1 + a =3a+1
4a - 5a - 3 =-a-3
- 5a + 7b + 6a =a+7b
6b - 6a + 2b =8b-6a
x - 4x = -3x
20 1 20
2010-04-15T13:41:49+02:00
3x + 2x = 5x
6x - x = 5x
- 8x + 5x = -3x
2a + 1 + a = 3a + 1
4a - 5a - 3 = -a - 3
- 5a + 7b + 6a = a + 7b
6b - 6a + 2b = -6a + 8b
x - 4x = -3x
2 4 2
2010-04-15T13:44:13+02:00
3x + 2x =5x
6x - x =5x
- 8x + 5x =-3x
2a + 1 + a =3a+1
4a - 5a - 3 =-a-3
- 5a + 7b + 6a =a+7b
6b - 6a + 2b =8b-6a
x - 4x = -3x
2 3 2